Agreement of Magnetic Resonance Imaging With Computed Tomography in the Assessment for Acute Skull Fractures in a Canine and Feline Cadaver Model - Hecht, Silke; Anderson, Kimberly M.; Castel, Aude; Griffin, John F.; Hespel, Adrien-Maxence; Nelson, Nathan; Sun, Xiaocun (Frontiers in Veterinary Science, 2021)
Computed tomography (CT) is the imaging modality of choice to evaluate patients with acute head trauma. However, magnetic resonance imaging (MRI) may be chosen in select cases. The objectives of this study were to evaluate the agreement of MRI with CT in the assessment for presence or absence of acute skull fractures in a canine and feline cadaver model, compare seven different MRI sequences (T1-W, T2-W, T2-FLAIR, PD-W, T2*-W, “SPACE” and “VIBE”), and determine agreement of four different MRI readers with CT data. Pre- and post-trauma CT and MRI studies were performed on 10 canine and 10 feline cadaver heads. Agreement of MRI with CT as to presence or absence of a fracture was determined for 26 individual osseous structures and four anatomic regions (cranium, face, skull base, temporomandibular joint). Overall, there was 93.5% agreement in assessing a fracture as present or absent between MRI and CT, with a significant difference between the pre and post trauma studies (99.4 vs. 87.6%; p < 0.0001; OR 0.042; 95% CI 0.034–0.052). There was no significant difference between dogs and cats. The agreement for the different MRI sequences with CT ranged from 92.6% (T2*-W) to 94.4% (PD-W). There was higher agreement of MRI with CT in the evaluation for fractures of the face than other anatomic regions. Agreement with CT for individual MRI readers ranged from 92.6 to 94.7%. A PD-W sequence should be added to the MR protocol when evaluating the small animal head trauma patient.